Analisis Suku Bunga SBI, Inflasi dan Nilai Tukar Rupiah Terhadap Harga Saham Sektor Consumer Goods Periode Tahun 2016-2020 - Deki Zulkarnain; Solihin Solihin; Mulyadi Nursi (Jurnal Sains Sosio Humaniora, 2022)
The capital market has an important role in the economy of a country, because the capital market illustrates the economic condition of a country. By looking at stock prices, especially stocks in the consumer goods sector, investors can estimate the level of economic growth in a country and the development of investment in a country. There are several macroeconomic variables that can affect stock price movements. In this study, the macro factors used are inflation, interest rates and the rupiah exchange rate. The data taken is closing price data for each independent and dependent variable. The sampling method used in this study was a saturated sample. The data used is secondary data with documentation data collection method. The analytical tool used is multiple linear regression. The research period taken is from 2016 - 2020. The results show that the exchange rate and interest rates have a positive and significant effect on stock prices in the consumer goods sector and inflation has a negative and significant effect on stock prices in the consumer goods sector.